Exploring impacts of COVID-19 from sport business manager's perspective - Rodrigues, T. (2020)
The unexpected outburst of COVID-19 has challenged the global sports economy in mass scale. Sport business and sport organisations have been affected tremendously from many perspectives. Sport business managers have been forced to take unforeseen actions due the rapid disruption of business models, cancelled events and lack of spectators in order to protect the businesses, athletes and even the public image. The aim of this research was to examine the level of strategic preparedness during the outbreak of global pandemic disease. The actual research problem was to clarify the managerial implications of this black swan event in sport business not only from financial perspective. The research was designed using qualitative approach and methods. Eight representatives from various types of sport organisations and countries were selected and primary data was collected using semi-structured interview. The data was analysed using content analysis method. Despite of the relatively small sample size, the findings indicated that sport business managers have been able to react with the reduction of costs and increased use of digital communication as managerial measures. An assumption of new ways of operating with digital technology towards more sustainable business models was recognized. Experiences of managers have been similar for private, non-profit and public sector organisations. New trends in customer behavior of sport fans were recorded. However there is a need for a long-term analysis in order to clarify the changes in business environment and managerial implications.